2020
DOI: 10.1111/jfpp.14940
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the pulsed electric field on physicochemical properties, fatty acid profiling, and metal migration of goat milk

Abstract: Goat milk is a prominent alternative to bovine milk, for having a great dietary and nutritional characteristic, particularly among nursing mothers and infants to alleviate milk allergy and other gastrointestinal problems (Zhou et al., 2014). Goat milk contains vitamins, minerals, proteins, and fatty acids that are quickly absorbed by the human body (Ravula & Ramachandra, 2016; Sousa et al., 2019). The functional properties and nutritional benefits of goat milk contribute to the expansion of the global goat mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…Previous studies on goat milk suggeested the heatdependent pasteurization methods, but the latest research proved that pulsed electric field treatment could be used as an alternative to the conventional pasteurization method to obtain better results. Goat milk treated with 20 kV/cm for a period of 5s showed similar results to conventional pasteurization, revealing its high potential for application as an alternative to conventional pasteurization method (92). Previous studies do not have definite information about the actual process and processing parameters for obtaining goat milk powder, but the study of Nascimento et al (59) suggested some parameters in spray drying and other aspects of the process, to obtain an end product with very low moisture content (2.4%) and water activity (0.2-0.3), enhancing the shelf life and consumer acceptability of goat milk powder (59).…”
Section: What Does the Current Review Add To The Existing Knowledge?mentioning
confidence: 71%
“…Previous studies on goat milk suggeested the heatdependent pasteurization methods, but the latest research proved that pulsed electric field treatment could be used as an alternative to the conventional pasteurization method to obtain better results. Goat milk treated with 20 kV/cm for a period of 5s showed similar results to conventional pasteurization, revealing its high potential for application as an alternative to conventional pasteurization method (92). Previous studies do not have definite information about the actual process and processing parameters for obtaining goat milk powder, but the study of Nascimento et al (59) suggested some parameters in spray drying and other aspects of the process, to obtain an end product with very low moisture content (2.4%) and water activity (0.2-0.3), enhancing the shelf life and consumer acceptability of goat milk powder (59).…”
Section: What Does the Current Review Add To The Existing Knowledge?mentioning
confidence: 71%
“…The particle size determination of milk samples was determined according to the method of Azizah et al (2020) by using a laser diffraction particle size alyser (M3000, Malvern Instruments Ltd, UK).…”
Section: Particle Sizementioning
confidence: 99%
“…Pulsed electric field (PEF) has gained more attention in the past few years to extract beneficial materials from food waste/by-products through diffusion, osmosis, pressing, and drying [ 10 ]. It minimizes the deleterious effects of conventional heating processes [ 11 , 12 , 13 ]. PEF technology, as a promising alternative to other methods (boiling, microwave- and ultrasound-assisted extractions, etc.…”
Section: Introductionmentioning
confidence: 99%